Fine particle matter (PM2.5) in the ambient air of Chiang Mai-Lamphun basin in northern Thailand - Narongpan Chunram (2018)
There are growing concerns about the air quality of the Chiang Mai-Lamphun Basin in northern Thailand with accelerating development, increased industrial emissions, expanding transportation, extensive open burning and the continuing drought. High levels of haze during the years 2004-2007 impose threats to human health and environmental management. Twenty-four-hour measurements of PM2.5particulate matter have been carried out during the two-year period June 2004 to May 2006. Samples were collected on 47 mm filters with the use of low volume gravimetric samplers, accompanied by meteorological data. The annual average mass concentration of PM2.5 was 35.6 μg/m3during June 2004 to May 2005 and 35.7 μg/m3during June 2005 to May 2006, higher than the USEPA daily limit. Concentrations in rainy, winter and summer seasons, June 2004 to May 2005, were 17.8, 52.3 and 36.4 μg/m3, respectively. Regression analysis was used to investigate the relationship among2.5, PM10inorganic gaseous pollutants (O3, NO2, SO2), and meteorological parameters.